Cerebrovascular disease at young age is related to mother's health during the pregnancy-The Northern Finland Birth Cohort 1966 study - Rissanen, Ina; Geerlings, Mirjam; Juvela, Seppo; Miettunen, Jouko; Paananen, Markus; Tetri, Sami (International Journal of Stroke, 2023)
Background and purpose For prevention of cerebrovascular diseases at younger age, it is important to understand the risk factors occurring early in life. We investigated the relationship between mothers' general health during pregnancy and the offspring's risk of cerebrovascular disease in age of 15 to 52 years. Methods Within the population-based prospective Northern Finland Birth Cohort 1966, 11,926 persons were followed from antenatal period to 52 years of age. Information on their mother's ill health conditions, i.e., hospitalizations, chronic diseases, medications, vitamin or iron supplement, fever, anemia, mood, and smoking was collected from 24th gestational week onwards. Ischemic and hemorrhagic cerebrovascular diseases of the offspring were identified from national registers in Finland. Cox proportional hazard models were used to estimate the association of mother's health conditions with incidence of cerebrovascular disease in the offspring, with adjustments for potential confounders. Results During 565,585 person-years of follow-up, 449 (2.8%) of the offspring had a cerebrovascular disease. Hospitalization during pregnancy was associated with an increased risk of cerebrovascular disease in the offspring (hazard ratio (HR) = 1.49; 95% confidence interval (CI) 1.06-2.08) after adjustment for confounders, as was having more than three ill health conditions (HR = 1.89; CI 1.14-3.11). Not using vitamin or iron supplement was associated with increased risk for cerebrovascular disease in the offspring (HR = 1.39; CI 1.01-1.89). Conclusions The results suggest that the risk of cerebrovascular disease may start as early as during the antenatal period, and the health characteristics of mothers during pregnancy may play a role in cerebrovascular disease risk of the offspring. Peer reviewed